Popliteal Artery Adventitial Cyst: case report and literature review - Frankini,Angelo (2012)
The popliteal artery adventitial cyst is not a commonly studied pathology due to the rarity of its occurrence, however it is a disease that should always be considered as a differential diagnosis in the presence of a young patient who complains of claudication of the lower limbs. Because of its importance, the aim of this paper is to review some concepts about this disease based on a case report, analyzing its occurrence, etiopathology, clinical manifestations, diagnosis and treatment options.